Biographical sketch of Dr. Reggie J. Laird Broom: pioneer of soil science in Mexico. - Espinosa Victoria, David (REVISTA TERRA LATINOAMERICANA, 2017)
Nearly three years after his death, the Mexican Society of Soil Science, A.C., through this review, pays posthumous tribute to the memory of one of the pioneers of Soil Science in Mexico. The work done by Dr. Reggie J. Laird Broom (Figure 1) over 45 years emphatically reflects his commitment to and passion for helping small farmers in Mexico, Latin America and the world.